Financial penalties in Islamic and Yemeni laws and their judicial applications / Abdo Abdullah Abdullah Saumaah - Saumaah, Abdo Abdullah Abdullah (2015)
This study aims at analyzing the legitimacy of financial penalties in the scope of Shari’ah and Yemeni law. It is also to show the significance of financial penalties at a public and private level, highlight its contemporary types and forms, show the relevance of Shari’ah to Yemeni law, and to what extent they are linked in legitimizing financial penalties, as well as stating the aspects of agreement and disagreement between Shari’ah and Yemeni law in this regard. Moreover, it aims at studying and analyzing the rulings of the most prominent Yemeni courts relating to financial penalties, identifying whether these rulings conform to Shari’ah and Yemeni law, and identifying the aspects of development and deficiency in the Yemeni judiciary. The methodology of this study is based on the analytical and deductive method, considering Shari’ah texts and analyzing the articles of law and their judicial rulings. Besides, this study is also based on the comparative approach, in which Shari’ah texts and texts of law and judicial rulings are compared, and stating the aspects of agreement and disagreement between them. Among other findings, the study has concluded that the financial penalty is legitimate in its various forms, either being fine, destruction, deprivation, or confiscation, in addition to its need at public and private level, in order to achieve security and stability for the society. The study has also found scarcity in the jurisprudent texts and statements in some contemporary issues of financial penalties. Therefore, Islamic jurisprudence needs to enrich such issues. Besides, the study has shown that Yemeni law conforms to Shari’ah in most cases of financial penalties, except for some cases in which no financial penalty is specified by law. Moreover, it has been found that Shari’ah and Yemeni law are agreed in authorizing the Yemeni judge to a broad authority to punish by financial penalties and determine their forms and amounts, and consequently, the state is authorized to apply so. Furthermore, the study has revealed that there is a low amount of money imposed in many crime issues, in which fines are governed. It has also been demonstrated that Yemeni legislator has heavily adopted prison sentences compared to financial penalties. Finally, the study has found that the Yemeni judicial rulings applied to financial penalties are conformed to Shari’ah and Yemeni law in all forms, except in two cases.